أثر الثقافة التنظيمية على الأداء التنظيمي في المؤسسات الخاصة دراسة ميدانية في مؤسسة تيسكوبا لنسيج الأغطية والقلاع بالقرارة –غرداية- - يوسف, اسماء (جامعة الوادي - University of Eloued, 2020)
This study aimed to identifying the effect of organizational culture on organizational performance in TISCOBA Textile enterprise for Covers and Castles in -GUERRARA –GHARDAIA This study was applied random sample consisting of) 60 (employees. To achieve the objectives of the study the researcher used questionnaire to collect data, the data were analyzed by using the statistical package for social sciences (Spss). Depending on the means, standard deviation, correlations coefficient, simple regression. The study concluded with the following results: There is statistically significant effect between organizational culture and organizational performance, this value increases the coefficient of correlation(R=0.792) and the relationship is positive because the coefficient of correlation is positive and medium, and the explanatory power of the model is reached (R 2=0.627)
The effect of organizational culture on organizational performance in private enterprises'-empirical study in TISCOBA Textile enterprise for Covers and Castles in -GUERRARA – GHARDAIA
مقال
Keywords: ثقافة تنظيمية ،أداء تنظيمي،مؤسسة تيسكوبا لنسيج الأغطية والقلاع –القرارة-غرداية.